KUASA PENGETAHUAN - Esha, Muhammad In’am (ULUL ALBAB Jurnal Studi Islam, 2010)
This paper studies about the relationship between power and (the will to gain) knowledge. It reviews such key points as that every human being has modalities of knowledge whose function depends on his/her will and that human being has the will to power in addition to the will to know. Both wills are inseparable. Human beings cannot reach the power without knowledge; and knowledge cannot be reached without strong will and modality of power. However, as this paper proposes, the will to power and the will to know are purposive; they are not without goal. In Islamic perspective, reaching a power is not for the power itself; rather, it should be directed to reach the ultimate goal of manifesting the ‘God values.’ Islam guides people toward the ‘ilahiyah power’ or ‘the Spirit of God’ as the ultimate goal of achieving power. As a result, the idea of power/knowledge should be completed by faith/power/knowledge relation.